Tradition, status, and experience orientations can be examined as indicators of basic dispositions alongside separate measures of economic capital, cultural capital, and parental migration background. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Tradition, status, and experience orientations can be examined as indicators of basic dispositions alongside separate measures of economic capital, cultural capital, and parental migration background.
iso-id: iso:argument:hQ78AmJt; sha256: sha256:2a46177f52ce65f8e979ee1d4c70af0ce2eec00859ba2553432eda654a69601d